Mining raw plant transcriptomic data for new cyclopeptide alkaloids - Kriger, Draco; Pasquale, Michael A.; Ampolini, Brigitte G.; Chekan, Jonathan R. (Beilstein Journal of Organic Chemistry, 2024)
In recent years, genome and transcriptome mining have dramatically expanded the rate of discovering diverse natural products from bacteria and fungi. In plants, this approach is often more limited due to the lack of available annotated genomes and transcriptomes combined with a less consistent clustering of biosynthetic genes. The recently identified burpitide class of ribosomally synthesized and post-translationally modified peptide (RiPP) natural products offer a valuable opportunity for bioinformatics-guided discovery in plants due to their short biosynthetic pathways and gene encoded substrates. Using a high-throughput approach to assemble and analyze 700 publicly available raw transcriptomic data sets, we uncover the potential distribution of split burpitide precursor peptides in Streptophyta. Metabolomic analysis of target plants confirms our bioinformatic predictions of new cyclopeptide alkaloids from both known and new sources.
Keywords: burpitides; natural products; plants; RiPPs; transcriptome mining